(untitled) (Research, Society and Development, 2021)
In The aim of the present study was to evaluate the association between sleep quality and screen time among adolescent students. A cross-sectional study was conducted with adolescents between 15 and 19 years of age at a public high school in the city of Recife, Brazil. Data were collected through digital questionnaires using the Google Forms tool: questionnaire addressing sociodemographic characteristics, Pittsburgh Sleep Quality Index (PSQI) and Electronic Media Questionnaire. Statistical analysis involved either Pearson’s chi-square test or Fisher’s Exact test, with a 95% confidence interval and 5% significance level. The sample consisted of 128 adolescents (mean age: 16.20 years; 62.5% female). Most participants (65.6%) slept eight or more hours per night and 62.5% considered their sleep quality to be good. Cellular phone use time ≥4 hours/day was associated with poor sleep quality. Associations were also found between poor sleep quality and use after 10 pm of computers [OR (95% CI): 10.6 (2.6 to 42.0); p (1) <0.001], social networks [OR (95% CI): 2.1 (2.4 to 16.1); p (1) <0.001] and television [OR (95% CI): 2.8 (1.2 to 6.2); p(1) = 0.011]. Nighttime use of digital screens and a screen time ≥4 hours/day were associated with poor sleep quality.